Perbandingan Kebijakan Fiskal dalam Perspektif Konvensional dan Islam: Telaah Teoritis dan Praktik Historis - Annisa Rakhma Dewi; Inggis Shalma Zahira; Vika Putri Nurwinda; Suci Hayati (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Fiscal policy is one of the main instruments used by the state to manage the economy, both in terms of expenditure and state revenue. This study aims to compare fiscal policy in conventional and Islamic perspectives with a descriptive-qualitative approach. In conventional economics, fiscal policy aims to maintain macroeconomic stability, promote growth, and income distribution through tax instruments and state spending. Meanwhile, in Islamic economics, fiscal policy is designed to achieve the maqashid of sharia, namely social justice, the welfare of the people, as well as equitable distribution of wealth without usury and unethical economic practices. This study also reviews the practice of fiscal policy during the time of the Prophet Muhammad and the Khulafaur Rashidin, which shows the implementation of the state financial system through Baitul Mal and other sources of revenue such as zakat, kharaj, fai, and jizyah. This research shows that although there are similarities in the objectives between the two systems, namely public welfare, there are fundamental differences in the philosophical approaches and policy instruments used. Thus, understanding both perspectives is important in designing a fair and sustainable fiscal policy, especially for Muslim-majority countries.